Strategies for Developing Women’s Entrepreneurship-Based Decision Factors and Business Model Analysis - Riska Awalia; Rizal Syarief; Teti Haryati (School of Business, IPB University (SB-IPB), 2026)
Background: Women play a vital role in Indonesia’s MSME sector, yet micro-scale food businesses in Bandung remain hindered by managerial limitations and resource constraints despite strong motivation and supportive policies. Understanding their entrepreneurial motives and business model patterns is therefore essential for improving business sustainability.Purpose: This study examines the conditions, decision-making factors, and business models of women micro entrepreneurs in Bandung, and formulates development strategies based on their motives and business model characteristics. Design/methodology/approach: Using a qualitative approach, this study employed purposive sampling, interviews, observations, and literature review. Data were analyzed using descriptive analysis, the Business Model Canvas, feedback grid, and SWOT. Findings/Result: The study finds that women’s micro-scale food enterprises in Bandung are shaped by personal and socio-economic motives, strengthened by unique value propositions but constrained by managerial and resource limitations, requiring integrated strategies in digitalization, capacity building, and ecosystem collaboration to support sustainable growth.Conclusion: A holistic, ecosystem-based approach, integrating mindset strengthening, digital utilization, managerial improvement, and strategic collaboration is crucial for enhancing the sustainability of women’s micro food enterprises.Originality/value (state of the art): This study offers novelty by integrating entrepreneurial motives with BMC, feedback grid, and expert-validated SWOT to develop a context-specific strategy model for women’s micro food businesses in Bandung. Keywords: women entrepreneurship, micro-scale food business, entrepreneurial motives, Business Model Canvas (BMC), feedback grid, SWOT analysis